SWI/SNF ATPase silenced HLF potentiates lung metastasis in solid cancers - Jin Zhou; Austin Hepperla; Jeremy M. Simon; Kangsan Kim; Qing Hu; Chuanhai Zhang; Lei Dong; Lianxin Hu; Cheng Zhang; Chengheng Liao; Alice Fang; Yayoi Adachi; et al. (Nature Communications)
Abstract Metastasis is the main cause of cancer-related deaths, yet the underlying mechanisms remain elusive. Here, using clear cell renal cell carcinoma (ccRCC), a tumor type with frequent lung metastases, we conduct an in vivo genome-wide CRISPR-Cas9 screen and identify HLF as a potent suppressor of lung metastasis. HLF depletion enhances ccRCC cell migration and lung metastasis, whereas HLF overexpression abrogates these effects. In ccRCC patients, HLF expression is reduced at metastatic sites and associates with epigenetic silencing mediated by the SWI/SNF ATPase subunit BRG1. HLF levels negatively correlate with migration potential in collagen. Mechanistically, HLF regulates LPXN expression, modulating the integration of collagen’s mechanical cues with the actin cytoskeleton through Paxillin, thereby suppressing cancer cell migration and lung metastasis. Overexpression of HLF or pharmacological inhibition of BRG1 reduces cell invasion across multiple cancer types. Our findings suggest that targeting the BRG1-HLF axis offers a promising therapeutic strategy for combating metastatic cancers.